2015
DOI: 10.5539/jps.v4n1p27
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Solanum Species (Solanum aethiopicum complex; Solanum macrocarpon and Solanum anguivi) Using Multiplex RAPD primers

Abstract: Genetic diversity of S. aethiopicum complex, S. macrocarpon and S. anguivi was investigated using molecular approach. Seeds were randomly secured across north central locations in Nigeria and planted. Nine (9) oligonucleotide primers were initially screened for their polymorphism from where five (5) polymorphic primers were selected. A total of twenty five (25) accessions were studied. DNA was extracted from each accession using FTA PlantSaver card method following standard protocol (Whatman®, 2014). Amplifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…When considering only SSR or SNP markers, accessions from different groups of the scarlet eggplant complex (i.e., S. anguivi, the Intermediate S. anguivi-S. aethiopicum group, and the four groups of S. aethiopicum) often shared a same profile. Our data are in agreement with those of other authors who used AFLPs and SSRs (Sunseri et al 2010), RAPDs (Aguoru et al 2015), and SNPs (Acquadro et al, 2017) and also found that accessions of S. aethiopicum did not cluster according to the cultivar group. This is an additional indication that these groups, which are distinguished on the basis of morphology (Lester, 1986;Lester and Daunay, 2003;Plazas et al 2014), are not genetically differentiated.…”
Section: Validation Of the Ssr And Snp Markers For Fingerprintingsupporting
confidence: 93%
“…When considering only SSR or SNP markers, accessions from different groups of the scarlet eggplant complex (i.e., S. anguivi, the Intermediate S. anguivi-S. aethiopicum group, and the four groups of S. aethiopicum) often shared a same profile. Our data are in agreement with those of other authors who used AFLPs and SSRs (Sunseri et al 2010), RAPDs (Aguoru et al 2015), and SNPs (Acquadro et al, 2017) and also found that accessions of S. aethiopicum did not cluster according to the cultivar group. This is an additional indication that these groups, which are distinguished on the basis of morphology (Lester, 1986;Lester and Daunay, 2003;Plazas et al 2014), are not genetically differentiated.…”
Section: Validation Of the Ssr And Snp Markers For Fingerprintingsupporting
confidence: 93%
“…Hence, polyploidy as a combination of new chromosome may lead to sympatric speciation where new species of distinct character may likely evolve. The same type of hybrid complexes was reported in eggplant (Solanaceae) which continuously gives rise to new species because of their interfertile nature [17]. Mechanism of unreduced pollen formation was proposed by [21] as responsible for the polyploidization of sweetpotato.…”
Section: Resultsmentioning
confidence: 71%
“…This is substantiated in their root colour differences (Figure 4(d)). Similar approach of classification was successfully adopted by [17] in the determination of phylogenetic relationship in eggplant molecular studies in north central Nigeria. The present study generally agrees with the views of most plant taxonomists that microanatomical features in plants are of huge taxonomic values [15] [18]- [20].…”
Section: Resultsmentioning
confidence: 99%
“…DNA extraction is the first step in the study of plant DNA as it precedes all other molecular activities [7] [8]. The two methods compared in this report extracted sufficient quantity of DNA from leaf samples.…”
Section: Resultsmentioning
confidence: 99%